Becoming Citizens: Racialized Conceptions of ESL Learners and the Canadian Language Benchmarks - Fleming, Douglas (Canadian Journal of Education/Revue canadienne de l’éducation, 2010)
In this article, I report a qualitative study that sheds light on how adult learners of English as a Second Language (ESL) are constructing new national identities in the context of the challenges associated with immigration. In particular, I trace how the common threads among their conceptions of citizenship compare with those embedded within official, national assessment, and curriculum documents. Using a broad questionnaire and a focused set of semi‐structured interviews at a large ESL site in British Columbia, my research reveals the gaps between the experiences of these immigrants and how these documents construct and position idealized and racialized conceptions of second language learners. Key words: Adult ESL; identity; immigration; assessment and curriculum documents; semi‐structured interviews; gap analysis; racialized conceptions; language learning; Lang‐ uage Instruction to Newcomers to Canada (LINC); language policy and planning Dans cet article, l’auteur présente une étude de cas qualitative qui permet de mieux com‐ prendre comment des adultes apprenant l’anglais à titre de langue seconde (ALS) se façon‐ nent de nouvelles identités nationales dans le cadre des défis associés à l’immigration. L’auteur analyse tout particulièrement de quelle manière les éléments communs de leurs conceptions de la citoyenneté se comparent à certains des thèmes des documents de curri‐ culum et d’évaluation officiels. Reposant sur un vaste questionnaire et une série ciblée d’entrevues semi‐structurées menées dans un grand centre d’ALS en Colombie‐ Britannique, cette recherche révèle les écarts entre les expériences de ces immigrants et la façon dont ces documents créent et positionnent des conceptions à la fois idéalisées et racia‐ lisées des personnes apprenant une langue seconde. Mots clés : adultes en ALS, identité, immigration, documents d’évaluation et de curricu‐ lum, entrevues semi‐structurées, analyse des écarts, conceptions racialisées, apprentissage d’une langue, Cours de langue pour les immigrants au Canada (CLIC), politique ‐et amén‐ agement linquistiques